2004
DOI: 10.1063/1.1734685
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent fatigue behaviors of ferroelectric ABO3-type and layered perovskite oxide thin films

Abstract: The temperature-dependent dielectric and ferroelectric fatigue behaviors of ABO3-type perovskite thin films Pb(Zr0.52Ti0.48)O3 (PZT) and Pb0.75La0.25TiO3 (PLT) and layered Aurivillius thin films SrBi2Ta2O9 (SBT) and Bi3.25La0.75Ti3O12 (BLT) with Pt electrodes are studied. The improved fatigue resistance of PZT and PLT at a low temperature can be explained by the defect-induced suppression of domain switch/nucleation near the film/electrode interface, which requires a long-range diffusion of defects and charges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Finally, we point out here that the rejuvenation effect of ferroelectric fatigue [26], which shows the recovery of the spontaneous polarization as well, is different from our results related to ferroelectric aging or de-aging. The difference is that ferroelectric aging involves a short-range diffusion process [6], while fatigue involves a long-range diffusion process [27].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we point out here that the rejuvenation effect of ferroelectric fatigue [26], which shows the recovery of the spontaneous polarization as well, is different from our results related to ferroelectric aging or de-aging. The difference is that ferroelectric aging involves a short-range diffusion process [6], while fatigue involves a long-range diffusion process [27].…”
Section: Discussionmentioning
confidence: 99%
“…The improved fatigue properties of BNTM at low T below 200 K can be explained by the weaker effect of domain wall pinning and unpinning. 25,26 The low density domain walls at low T can suppress the domain pinning and make the diffusion of defects and charges more difficult. Thus the dependence of fatigue behaviors on T is weak.…”
Section: (A) and (B) It Can Be Found That The Dependences Ofmentioning
confidence: 99%
“…It has been reported that the fatigue behavior correlates to the defect traps at domain boundaries. 22,23 Because the off-stoichiometric SBT buffer layers in the present study have little influence on the composition of superposed SBT film ͑Fig. 3͒, the SBT/buffer capacitors could retain fatigue-free characteristics ͑Fig.…”
Section: Resultsmentioning
confidence: 94%